Geomorphic characteristics in the area of Mashoura Dagh and their relationship to land uses - CHTHWAN, MOHAMMED (Al-Adab Journal, 2023)
The importance of geomorphic studies emerged through their great and wide impact on the overall activities and natural and human phenomena, and for the purpose of proving this impact, the study came to the area of Mashoura Dagh, which is located (100 km) to the city of Mosul within the district of Tal Afar. The study began as a start to identify the most important geomorphic characteristics in the area through many field visits and access to geological and topographical maps of the area as well as the use of geographical techniques such as programs and satellite images. Where the nature of the formation of the area and its geological characteristics were determined, in addition to studying the climate by collecting data (40) years from the date of 1/1/1981 to 12/13/2021, leading to the identification of the surface characteristics of heights and ground slopes, the quality and susceptibility of the soil, and the nature of the water valleys. in the area. It turns out that these geomorphic characteristics have a clear and significant impact on each other and on the geographical and geomorphic nature of the area. After that, the study area was classified as a oriented classification for the purpose of identifying the most important land uses in it, based on the satellite image (Sentinel 2) with a resolution of (20 m) and captured on 4/9/2022. It was found that there are several types of land uses, the most important of which are agricultural, residential, abandoned, barren and wet lands. In order to find the relationship between geomorphic characteristics and land uses in the study area, the linear regression equation (OLS) was used to predict the value of the dependent variable, which is affected to varying degrees by the value of the independent variables. The results showed that there are three levels of relationship between geomorphic characteristics and land uses represented by strong, medium and weak relationships.